Moving into the future : national physical education standards : a guide to content and assessment - National Association for Sport and Physical Education (Boston, Mass : WCB McGraw-Hill, 1995)
A guide for the even grades K-12.
Cover subtitle: National standards for physical education : a guide to content and assessment.
Includes bibliographical references (p. 125).
Keywords: Physical education for children -- Standards -- United States; Physical education for children -- United States -- Evaluation; Physical fitness for children -- Standards -- United States; Physical fitness for children -- United States -- Evaluation